CtBP-dependent activities of the short-range Giant repressor in the Drosophila embryo - Nibu, Yutaka (The National Academy of Sciences, 2001)
There are at least three short-range gap repressors in the precellular Drosophila embryo: Krüppel, Knirps, and Giant. Krüppel and Knirps contain related repression motifs, PxDLSxH and PxDLSxK, respectively, which mediate interactions with the dCtBP corepressor protein. Here, we present evidence that Giant might also interact with dCtBP. The misexpression of Giant in ventral regions of transgenic embryos results in the selective repression of eve stripe 5. A stripe5-lacZ transgene exhibits an abnormal staining pattern in dCtBP mutants that is consistent with attenuated repression by Giant. The analysis of Gal4-Giant fusion proteins identified a minimal repression domain that contains a sequence motif, VLDLS, which is conserved in at least two other sequence-specific repressors. Removal of this sequence from the native Giant protein does not impair its repression activity in transgenic embryos. We propose that Giant-dCtBP interactions might be indirect and mediated by an unknown bZIP subunit that forms a heteromeric complex with Giant. We also suggest that the VLDLS motif recruits an as yet unidentified corepressor protein.